Pre regular pc-I-open sets in ideal topological spaces (2021)
In this paper, we introduce and study the notion of pre regular pc-I-open set on an ideal topological space. Besides, we show some of its properties. On the other hand, we define new variants of continuity and contra- continuity, indeed we show some characterizations and we prove some results on pre regular pc-I-connected, pre regular pc-I-T1, pre regular pc-I-T2 and pre regular pc-I-normal spaces.